Peran Gereja Membela Kemanusian Anak Marjinal: Upaya Teologi Transformasi Pelayanan Holistik - Lado, Gatsper A. (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
The marginal impact of poverty is an indicator of a beginning to lead to other social problems. One of the social problems caused by poverty is the rampant phenomenon of street children. This economic powerlessness causes children to be forced to join in looking for money by taking to the streets. From this, there are many incidents that make marginal children experience things that are not in accordance with values and laws. So the author describes the role of the church as a goal in strengthening believers in defending the humanity of marginalized children as an effort to transform Holistic ministry of theology. Using descriptive qualitative research methods, it can be concluded that the role starts with believers or churches practicing the values of humanity that must be humanized, because it is a principle of Humanism in biblical teaching that must be done sincerely for fellow humans. Furthermore, there are efforts by the Church and the Humanity of Marginal Children in Holistic service for Others to do good and be a light to the world.AbstrakMarginal akibat dari kemiskinan menjadi indikator dari sebuah awal untuk mengarahkan kepada permasalahan sosial lainnya. Salah satu masalah sosial akibat kemiskinan adalah maraknya fenomena anak jalanan. Ketidakberdayaan ekonomi tersebut menyebabkan anak terpaksa ikut mencari uang dengan cara turun ke jalan. Dari hal tersebut banyak kejaidan yang membuat anak marginal mengalami hal yang tidak sesuai dnegan nilai dan hukum. Maka penulis mendeskripsikan peran gereja sebagai tujuan dalam menguatkan orang percaya dalam membela Kemanusian anak marjinal sebagai upaya Teologi transformasi pelayanan holistik. Mengunakan metode penelitian kualitatif deskritif maka dapat disimpulkan bahwa peran tersebut dimulai dari orang percaya atau gereja mengamalkan nilai dari kemanusiaan yang harus dimanusiakan, sebab hal itu sebagai prinsip Humanisme dalam pengajaran Alkitabiah yang harus di kerjakan dengan tulus bagi sesama manusia. Selanjutnya adanya upaya Gereja dan kemanusiaan anak marginal dalam pelayanan Holistik bagi Sesama untuk mengerjakan kebaikan dan menjadi terang bagi dunia.